The Impact of Western Colonization on Islamic Countries: An Analysis of the Struggle for Independence - Hartinawanti Hartinawanti; Anwar Abu Bakar; Mayani Mayani; Muh. Ade Saputra; Rahmawati Rahmawati (ALSYS, 2025)
Western colonization of Islamic countries produced complex and interwoven transformations across political, economic, social, and cultural domains. This article presents a comprehensive literature review to analyze the multidimensional impacts of colonial rule, highlighting how colonization facilitated resource exploitation, dismantled indigenous governance structures, and imposed foreign legal systems that continue to shape post-colonial economic dependencies. Socially, colonial administrations restructured educational systems by introducing Western curricula, institutionalizing colonial languages, and advancing cultural Westernization. Despite these systemic changes, Islam remained a central force of ideological resilience, offering moral legitimacy and organizational frameworks for anti-colonial resistance. The religion served as both a unifying identity and a source of mobilization against colonial domination. Case studies illustrate the varied expressions of Islamic resistance: in Indonesia and Algeria, Islamic discourse legitimized jihad and armed struggle; in Egypt, it fostered reformist and political movements such as the Muslim Brotherhood; and in the Indian subcontinent, it constituted a foundational element in the political advocacy for the establishment of Pakistan. These cases underscore Islam’s contextual adaptability and its capacity to generate diverse responses to colonial challenges. The study contributes to a deeper understanding of the enduring socio-political and ideological legacies of colonialism in Islamic societies.